Hepatic and pulmonary macrophage activity in a mucosal challenge model of Ebola virus disease - Wanninger, Timothy G.; Saldarriaga, Omar A.; Arroyave, Esteban; Millian, Daniel E.; Comer, Jason E.; Paessler, Slobodan; Stevenson, Heather L. (Frontiers in Immunology, 2024)
The inflammatory macrophage response in Ebola virus disease is thought to contribute to severe disease, with liver and lung injury in humans. We sought to further define the activation status of hepatic and pulmonary macrophage populations in Ebola virus disease by comparing liver and lung tissue from terminal Ebola virus (EBOV)-infected and uninfected control cynomolgus macaques challenged via the conjunctival route. Gene and protein expression was quantified using the nCounter and GeoMx Digital Spatial Profiling platforms. Macrophage phenotypes were further quantified by digital pathology analysis. Hepatic macrophages in the EBOV-infected group demonstrated a mixed inflammatory/non-inflammatory profile, with no differences in M1/M2 gene expression compared to controls. Upregulation of CD163, a protein associated with macrophage activation syndrome, was observed in this population. Hepatic macrophages also showed differential expression of monocyte/macrophage differentiation, antigen presentation, and T cell activation gene sets, which were associated with decreased MHC-II allele expression. Moreover, hepatic macrophages had enriched expression of genes and proteins targetable with known immunomodulatory therapeutics, including S100A9, IDO1, and CTLA-4. The significant changes that occurred in both the liver and lung were more pronounced in the liver. These data demonstrate that hepatic macrophages in terminal conjunctivally challenged cynomolgus macaques may express a unique inflammatory profile compared to other macaque models and that macrophage-related pharmacologically druggable targets are expressed in both the liver and the lung in Ebola virus disease.